Molecular analysis of a stress-induced cDNA encoding the translation initiation factor, eIF1, from the salt-tolerant wild relative of rice, Porteresia coarctata - Latha, Rangan; Salekdeh, G. Hosseini; Bennett, John; Swaminathan, Monkumbu Sambasivan (Commonwealth Scientific and Industrial Research Organisation, 2004)
The analysis of plant response to stress is an important route to the discovery of genes conferring stress tolerance. Protein synthesis is very sensitive to salt stress and proteins involved in this process may be an important determinant of salt tolerance. The halophytic plant, Porteresia coarctata Tateoka, is a close relative of Oryza sativa L., and has the ability to withstand sudden changes in the soil salinity. The translation initiation factor 1 (PceIF1) cDNA was isolated from the leaves of P. coarctata that had been subjected to a high-salt treatment (150 mm NaCl). An expression study showed that the abundance of eIF1 transcripts increased to a maximum level 5 d after stress induction and then decreased to levels similar to leaves of control (unsalinised) plants. This gene was also up-regulated in exogenous abscisic acid (ABA) and mannitol treatments, suggesting that its induction is related to the water deficit effect of high salt. Our studies showed that expression levels of eIF1 transcripts might form a convenient indicator for monitoring a stress-responsive mechanism that operates in the leaves of P. coarctata.